A bibliometric analysis and review on the performance of polymer-modified bitumen - Alnadish, Adham Mohammed; Katman, Herda Yati Binti; Ibrahim, Mohd Rasdan; Gamil, Yaser; Mashaan, Nuha S. (Frontiers in Materials, 2023)
The addition of polymer to a base binder has been documented as a successful approach in terms of improving physical and rheological properties of the base bitumen. However, the main drawbacks of polymer-modified bitumen are incompatibility and degradation of polymer due to aging. This article aims to introduce a bibliometric analysis and review on modifying bitumen with polymers. Additionally, this article intent to highlight the significant gaps and recommendations for future work. Furthermore, another objective of this article is to provide a worth attempt regrading reducing the negative impact of polymer's drawbacks on the performance of polymer-modified base binder. The findings of this article demonstrated that the test of storage stability for polymer-amended bitumen should be modified, in which the softening point of aluminum tube centerpiece should be measured to introduce a better evaluation for the storage stability of polymeramended bitumen. In addition, the effects of kinetic factors (mixing sequence, viscosity of blend, shear rate, and time of mixing) on the compatibility of polymer-amended bitumen should be investigated. Moreover, the addition of compatibilizers and stabilizers to polymer-modified binder is recommended to improve compatibility and reduce the effect of aging on degradation of polymer.